Psychological characteristics of persons who are liable to suffer from myocardial infarction - Goštautas, A. (Psichologija, 1982)
The results of investigation of 5,114 males from population aged from 40 through 59 by using methods of standardized interview for the diagnosis of type A behaviour pattern, standardized questionnaire about attitudes towards health and MMPI were analysed. Persons exhibiting type A behaviour revealed sickness in their attitudes, were less psychologically adapted on MMPI scales, had higher scores on Reeder's Stress Scale.
Keywords: health; attitudes; myocardial infarction; type A behaviour pattern; personality